Oral vaccination via virus-like particles encapsulated in Lactococcus lactis - Hui Yee Hong; Lee Ching Pei Carmen; Pin Xuan Chee; Lim Xin Ying; Zhi Wei Wong; Janlin Chan; Mookkan Prabakaran; Daiwen Yang (Fish & Shellfish Immunology, 2026)

Traversing the Valley of Death for nanotechnology-based natural products: strategies and insights from pharmaceutical stakeholders - Jian Sheng Loh; Chan Yew Low; Wei Peng Low; Yun Lin Ng; Wen Qi Mak; Li Kar Stella Tan; Hong Hao Chan; Yong Sze Ong; Stephanie Kay Ann Cheah; Emmellie Laura Albert; Chee Wun How (Drug Delivery and Translational Research, 2025)

Utilization of a monoclonal antibody targeting the functional P-domain of Nervous Necrosis virus (NNV) coat protein: Developing an epitope-blocking ELISA to quantify viral neutralizing antibodies - Lee Ching Pei Carmen; Janlin Chan; Si Qi Lee; Hui Yee Hong; Ping Xuan Chee; Yang Song; Daiwen Yang; Mookkan Prabakaran (Aquaculture, 2025)

Improvement of the Diagnostic Method for the Detection of Parasite Eggs Using the Formalin Ethyl Acetate Concentration Technique - Jia-Hung Liou; Te-Ling Lu; Hui-Fen Cheng; Long-Wei Lin; Po-Cheng Kung; Hong-Jing Chuang; Te-Hsiu Lee; Chee-Hong Chan; Te-Jung Lu (Acta Parasitologica, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Mechanical and Clinical Evaluation of a Shape Memory Alloy and Conventional Struts in a Flexible Scoliotic Brace - Wing-Yu Chan; Joanne Yip; Kit-Lun Yick; Sun-Pui Ng; Lu Lu; Kenneth Man-Chee Cheung; Kenny Yat-Hong Kwan; Jason Pui-Yin Cheung; Kelvin Wai-Kwok Yeung; Chi-Yung Tse (Annals of Biomedical Engineering, 2018)

Transcriptional responses of the marine green alga Micromonas pusilla and an infecting prasinovirus under different phosphate conditions - Charles Bachy; Christina J. Charlesworth; Amy M. Chan; Jan F. Finke; Chee‐Hong Wong; Chia‐Lin Wei; Sebastian Sudek; Maureen L. Coleman; Curtis A. Suttle; Alexandra Z. Worden (Environmental Microbiology, 2018)
Summary Prasinophytes are widespread marine algae for which responses to nutrient limitation and viral infection are not well understood. We studied the picoprasinophyte, Micromonas pusilla , grown under phosphate‐replete (0.65 ± 0.07 d −1 ) and 10‐fold lower (low)‐phosphate (0.11 ± 0.04 d −1 ) conditions, and infected by the phycodnavirus MpV‐SP1. Expression of 17% of Micromonas genes in uninfected cells differed by >1.5‐fold ( q

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A population-based LD map of the human chromosome 6p - Hong Xiang Yu; Jer-Ming Chia; Guillaume Bourque; Marie Vivien Wong; Soh Ha Chan; Ee Chee Ren (Immunogenetics, 2005)